2018
DOI: 10.1007/s11207-018-1338-x
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of the Height Dependence of Magnetic Fields in Sunspots

Abstract: To understand the physics of sunspots, it is important to know the properties of their magnetic field, and especially its height stratification plays a substantial rôle. There are mainly two methods to assess this stratification, but they yield different magnetic gradients in the photospheric layers. Determinations based on the different origin of several spectral lines and the slope of their profiles result in gradients of −2 to −3 G km −1 , or even steeper. This is similar for the total magnetic field streng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Recently, Balthasar (2018) presented an extensive review about the unsolved problems of the estimation of the magnetic field gradient in sunspots, exploring the different techniques employed and the reasons for the discrepancy of the results presented in the literature. For example, Rueedi et al (1995) found that the vertical gradient of the magnetic field decreases outwards in the sunspot, with values of 0.1-0.3 G km −1 in the outer penumbra, and with the height in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Balthasar (2018) presented an extensive review about the unsolved problems of the estimation of the magnetic field gradient in sunspots, exploring the different techniques employed and the reasons for the discrepancy of the results presented in the literature. For example, Rueedi et al (1995) found that the vertical gradient of the magnetic field decreases outwards in the sunspot, with values of 0.1-0.3 G km −1 in the outer penumbra, and with the height in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…4 of Khomenko & Collados (2007). As the field strength there is on the order of one thousand gauss, with a difference of about 300 G between the two line measurements, leading to the vertical gradient value of 3 G km −1 , as reported by Balthasar (2018), the 10 G inaccuracy on the longitudinal field is much smaller than the finite difference of the measurements. The horizontal gradient is found to be only about 0.3 G km −1 , which corresponds to the reversal of a 1500 G typical horizontal component from one side to the other of a sunspot with a typical diameter of 10 000 km.…”
Section: Introductionmentioning
confidence: 64%
“…The problem of the large magnitude difference between the observed horizontal and vertical magnetic field gradients in and around sunspots has been known for a long time. Balthasar (2018) wrote a detailed review of observations, where it is shown that typical values of 3 G km −1 and 0.3 G km −1 are obtained for the vertical and horizontal gradients of the magnetic field, respectively, regardless of the telescope, spectral line(s), and measurement interpretation method used. Using these values would surprisingly lead to a non-zero divergence of the observed magnetic field, which is a priori not acceptable.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations